Digital technologies for control of heat cooling supply systems at industrial facilities: increasing efficiency, economy and reliability - Mashchanova, T. R.; Ormanbekova, A. A.; Nugmanova, S. A. (Харківський національний автомобільно-дорожній універститет, 2024)
Currently, industrial facilities are facing increasing demands on the efficiency, reliability and cost-effectiveness of heat and cooling systems. The article discusses the use of modern digital technologies to control such systems. SCADA systems, IoT sensors and predictive analytics play an important role in optimizing heat and cold supply management processes at industrial facilities.
Keywords: SCADA system; IoT sensors; 697.34